Calcium Chloride vs. Mechanical Preparation of Fibrinogen-Depleted Human Platelet Lysate: Implications for Umbilical Cord Mesenchymal Stem Cell Culture - Yen Theng Lim; Muttiah Barathan; Yu Ling Tan; Yi Ting Lee; Jia Xian Law (Life)
Fetal bovine serum (FBS) has long been the standard supplement in cell culture media, providing essential growth factors and proteins that support cell growth and differentiation. However, ethical concerns and rising costs associated with FBS have driven researchers to explore alternatives, particularly human platelet lysate (HPL). Among these alternatives, fibrinogen-depleted HPL (FD-HPL) has gained attention due to its reduced thrombogenicity, which minimizes the risk of clot formation in cell cultures and enhances the safety of therapeutic applications. This study investigates two preparation methods for FD-HPL from human platelet concentrates: the calcium chloride method and a mechanical approach. The concentrations of critical growth factors, including vascular endothelial growth factor (VEGF), brain-derived neurotrophic factor (BDNF), insulin-like growth factor (IGF), and keratinocyte growth factor (KGF), were evaluated for both methods. Additionally, the impact of FD-HPL on the proliferation and morphology of umbilical cord-derived mesenchymal stem cells (UC-MSCs) was assessed. The findings revealed that the calcium chloride method produced significantly higher concentrations of all measured growth factors compared to the mechanical method. Moreover, UC-MSCs cultured in calcium chloride-prepared FD-HPL exhibited enhanced cellular characteristics, including increased cell size, elongation, and improved overall morphology compared to those cultured in mechanically processed FD-HPL. These results indicate that the preparation method significantly influences the biological properties of HPL and the effectiveness of UC-MSC culture. The calcium chloride method emerges as a superior technique for producing FD-HPL, offering a promising alternative to FBS in regenerative medicine applications. This study underscores the importance of preparation methods in optimizing HPL for cell culture and therapeutic uses.